COVID-19 – sharing experiences of Medical Universities: Report on an International Seminar on 12 May 2020 - Ataniyazova, Oral A; Moshammer, Hanns; Yari, Saeed; Ivanov, Dmitry; Jarrahi, Alireza Mosavi (Asian Pacific Journal of Environment and Cancer, 2020)
The Medical University of Karakalpakstan in Nukus, Uzbekistan, as host, in collaboration with the Medical University of Vienna, Austria, and the Saint-Petersburg State Pediatric Medical University from Russia, in May 2020 organized an online seminar with the title “COVID-19 – sharing experiences of Medical Universities”. Indeed the pandemic has hit many countries throughout the world with unexpected force and healthcare systems often were not prepared. That experience clearly showed the need for international cooperation and coordination. It was a sad observation that instead often mistrust and national egoism prevailed.